Studi Keterdapatan Unsur Logam di Daerah Kampung Nafri, Distrik Abepura, Kota Jayapura, Papua - Maya Falentina I Msiren; Endang Hartiningsih; Karl Karoluz Wagab Meak (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This research aims to identify the presence of metal elements in sandstone, laterite and clay minerals from Nafri Village, Abepura, Jayapura. The method used is X-Ray Fluorescence (XRF) at the Hydrology and Hydrogeochemistry Laboratory, ITB Bandung. Three field samples (ST-1, ST-2, ST-3) showed significant metal content. ST-1: contains, Fe(28.7%), Mn(0.0761%), Ti(0.692%), Ni(0.0297%), Cr(0.0907%), Na(trace), Mg(1.95%), Al(21.5 %), Cu(0.0565%), Zn(0.0294%), Rh(0.554%) ;ST-2 contains Na(0.493%), Mg(1.07%), Al(4.55%), K(0.801%), Ca (62.6%), Ti(0.364%), Mn(0.148%), Fe(14.0%), Cu(0.0342%), Sr(0.218%), Ag(0.135%); and ST-3 contains Na(0.625%), Mg(1.38%), Al(3.87%), K(0.937%), Ca(64.5%), Ti(0.409%), Mn(1.38%), Fe(7.37%). %), Sr(0.305%). The results show potential metal resources, particularly nickel and iron, in the area for further exploration and mining. This research provides important basic information for the study of geology and resource management in Jayapura